Terms of trade and output fluctuations in Colombia - Gonzalo Hernández (University of Massachusetts, Department of Economics, 2011)
This paper explores the importance of the terms of trade to explain output fluctuations in Colombia, a developing country where almost 60% of the exports correspond to four commodities: oil (32%), coal (17%), coffee (5%) and nickel (2%), and where 80% of its imports are intermediate and capital goods. This research is motivated fundamentally by the particular importance of short run fluctuations in developing economies, the fact that the Colombian terms of trade are procyclical and the current debate in Colombia about eventual economic policies toward sterilization of the effects of changes in commodities prices in a context of an appreciation of the nominal exchange rate. The study includes a time series analysis, for the period 1994-2009 with quarterly data, which follows the Box-Jenkins methodology for an ARMAX model. I find robust evidence that indicates that the quarterly growth of GDP is positively and significantly affected by variations in the terms of trade, which explain 1/3 of GDP growth variability. This result is consistent with the possible outcome of the three-goods model for an open small economy in which the terms of trade can be the source of the aggregate output fluctuations.
Keywords: 330